291 IMPACT OF A RURAL COMMUNITY-BASED ALL-TERRAIN VEHICLE SAFETY CAMPAIGN. Issue 1 (1st January 2007) - Aitken, M. E.; Mullins, H. M.; Nixon, J.; Parnell, D. M.; Dick, R.; Graham, J.
Abstract : Background: All-terrain vehicles (ATVs) are associated with substantial risk of injury for children. Despite legislative and other public health efforts, ATV use by children continues and serious injuries are common. We developed and implemented a community-based ATV injury prevention program targeting rural youth designed to improve awareness and change behavior. Methods: Focus group input about effective safety themes was combined with data demonstrating injury risk factors to design the campaign. A variety of media and educational strategies were implemented in a high-risk county in rural Arkansas. Surveys documenting reported ATV safety behaviors were conducted in the local public schools prior to and after the campaign in the target county and also in a separate comparison high-risk county where no intervention was undertaken. Results: A total of 1, 950 survey responses were obtained from youth ages 9 to 18 years. ATV use in the previous year was reported in 1, 533 (79%). Household exposure to ATVs among young children was commonly reported, with 220 (14%) reporting use by children ages 0 to 6 years, 697 (45%) reporting use by 7 to 12 year olds, and 797 (52%) reporting use by 13 to 15 year olds. Riding with passengers was reported by 1, 267 youth (90.5%). Helmet use was reported in only 226 (15%), and only 825 (54%) wore any protective gear. Reports of ATV safety education and recollection of ATV safety information exposure increased in the intervention county compared with the comparison county. Protective equipment use was also somewhat increased in the intervention county (46% pre; 55% post) relative to the comparison (52% pre; 58% post). Other risk factors did not change in the short-term follow-up. Conclusions: ATV use and high-risk behaviors were common in the population of both counties. Preliminary results indicate that the campaign was effective in reaching many of the target youth. Reported safety behavior in the intervention county was not changed in the short term; however, a trend toward increased use of protective equipment was found. Long-term efforts and novel approaches to ATV safety may be required to combat ATV injury.